Given an integer partition $\lambda=(\lambda_1,\dots,\lambda_{\ell(\lambda)})$ of $n$ where $\ell(\lambda)$ is the length of $\lambda$, associate its conjugate partition $\lambda'$. Denote by $\lambda''=\lambda',0$ found by appending one extra zero at the right end of $\lambda'$. Further, define the following two numerics $a(\lambda'')_j=\lambda_j''-\lambda_{j+1}''$ for $j=1,2,\dots,\ell(\lambda')$ and also that $b(\lambda'')=\#\{j: a(\lambda'')_j>0\}$.

For example, if $\lambda=(4,2,1)$ then $\lambda'=(3,2,1,1)$ and $\lambda''=(3,2,1,1,0)$ and $a(\lambda'')=(1,1,0,1)$ and $b(\lambda'')=3$.

QUESTION. If $n=2^m$ then are these two polynomials equal? $$\sum_{\lambda\vdash n}(q-1)^{2b(\lambda'')}q^{n-\ell(\lambda)} \prod_{a(\lambda'')_j\geq1}\frac{q^{2a(\lambda'')_j}-1}{q^2-1}=(q-1)(q^{2n-1}-1).\tag1$$

Remark 1. To get some motivation, consider dividing the left-hand side of (1) by $(q-1)^2$, for any $n\in\mathbb{N}$. Taking the limit $q\rightarrow1$ in the resulting expression forces $b(\lambda'')=1$ which means the corresponding Young diagram of the partition $\lambda'$ (hence $\lambda$ itself) must be rectangular. Therefore, the final expression equals the sum of divisors (arithmetic) function $$\sum_{d\,\vert\, n}d.$$

Remark 2. I also observe that if $q\rightarrow-1$ in (1), then the left-hand side counts the number of ways of writing $n\in\mathbb{N}$ as a sum of two squares, which is this sequence $r_2(n)$.

  • 2
    $\begingroup$ Some powers of $q-1$ cancel in the l.h.s. to become: $$\sum_{\lambda\vdash n} q^{n-\ell(\lambda)} \prod_{a(\lambda'')_j\geq1}\frac{(q^{2a(\lambda'')_j}-1)(q-1)}{q+1}$$ $\endgroup$ Feb 28, 2020 at 2:12
  • $\begingroup$ @MaxAlekseyev: that's nice. $\endgroup$ Feb 28, 2020 at 2:56
  • $\begingroup$ Is this true for $n \neq 2^m$ too? $\endgroup$ Feb 28, 2020 at 23:29
  • $\begingroup$ Equation (1) seems true for $n=2^m$ while Remark 1 and 2 should hold for any $n\in\mathbb{N}$. Does that answer your question? $\endgroup$ Feb 29, 2020 at 2:17

1 Answer 1


Yes, your identity $(1)$ is true. We can give a proof as follows:

Let's denote the left hand side of your identity $(1)$ by $A_n(q)$. Starting with the identity $$\prod_{i\geq 1}\left(1+\sum_{r\geq 1}a_r(x_1x_2\cdots x_i)^r\right)=\sum_{\lambda}\left(\prod_{j\geq 1}a_{\lambda_j-\lambda_{j+1}}\right)\left(\prod_{j\geq 1}x_j^{\lambda_j}\right)$$ where $a_0$ is taken to be $1$, and the $a_i, x_i$ are formal variables, we make the substitutions $a_r=(q-1)^2\frac{q^{2r}-1}{q^2-1}$ for $r\geq 1$, $x_1=t$ and $x_i=qt$ for $i\geq 2$. This turns the right hand side into a generating function for the $A_n(q)$ where $A_0(q)$ is taken to be $1$. More specifically it gives $$\sum_{n\geq 0}A_n(q)t^n=\prod_{i\geq 1}\left(1+(q-1)^2\sum_{r\geq 1}\frac{q^{2r}-1}{q^2-1}(q^{i-1}t^i)^r\right)=\prod_{i\geq 1}\frac{(1-q^it^i)^2}{(1-q^{i-1}t^i)(1-q^{i+1}t^i)}$$ $$=(1-q)\frac{(qt;qt)^2_{\infty}}{(t;qt)_{\infty}(q;qt)_{\infty}}.$$ This final product has a Hecke-Rogers type expansion that was given by Andrews in "Hecke modular forms and the Kac-Peterson identities" (see Lemma 1).Using this expansion we get $$\sum_{n\geq 0}A_n(q)t^n=(1-q)\sum_{N\in \mathbb Z, r\geq |N|}(-1)^{r+N}q^{-N}(qt)^{\frac{(r+N)(r-N+1)}{2}}$$ and if we focus on $n=2^m$ we notice that the only way we can have $(r+N)(r-N+1)=2^{m+1}$ is if $(r,N)=(2^m,2^m)$ or $(r,N)=(2^m, 1-2^m)$. This means that $$A_{2^m}(q)=(1-q)(1-q^{2^{m+1}-1})$$ as desired. The observations in the remark can also be deduced from this last summation.

  • $\begingroup$ Great job, thank you. $\endgroup$ Mar 2, 2020 at 15:09

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.